REALITAS SOSIAL SIBER KOMUNIKASI GURU DALAM PEMBELAJARAN DARING : SMK WIDYA PATRIA 2 - Tandaju, Christina; Koli, Nicodemus (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
Through the Ministry of Education and Culture, the government is taking firm steps to break the chain of the spread of the virus, especially to children, by closing schools and moving teaching and learning activities at home or blindly. This firm decision taken by the government was not without risk, but it had to be taken considering that schools are locations that are prone to the spread of cluster viruses. The teacher, as a school liaison, becomes a liaison, namely, community relations from the school to its students. For this reason, this study aims to determine the social reality of teacher cyber communication in courageous learning at Widya Patria 2 Vocational School. In this study, descriptive methods and qualitative studies were used, namely looking at teacher communication strategies in online teaching through the concept of cyberculture with three perspectives, namely the perspective material, symbolic, and student experiences, so that they are motivated to study during a pandemic. Methods of data collection or information retrieval is done by literature study, interviews, and searches from the internet. This research is expected to be an evaluation and learning of cyberculture which becomes a cyber social reality at the Technology Preparedness Level, and for evaluation in brave learning so that brave learning can be adapted and followed by teachers and students in communicating.